ANALYSIS OF MOTIF AND PHILOSOPHICAL MEANING OF KUANTAN SINGINGI BATIK - Dewi, Puti Andam; Oktavinoarti, Della; Wulandari, Saftika; Tursina, Intan; Syukri, Apdanil (VCoDe : Visual Communication Design Journal, 2025)
This inquire about analyzes the themes and philosophical meaning of Kuantan Singingi Batik, a social legacy starting from Kuantan Singingi Rule, Riau Territory, Indonesia. Kuantan Singingi Batik is known for its unmistakable and significant themes that reflect the social values and reasoning of the nearby community. This inquire about points to recognize different themes found in Kuantan Singingi Batik and uncover the philosophical meaning contained in that. The inquire about strategy utilized is graphic subjective with an ethnographic approach. Information was gotten through coordinate perception, in-depth interviews with neighborhood batik creators and social figures, as well as writing considers. Perceptions were carried out to watch the batik making prepare and archive the different themes utilized. In-depth interviews point to investigate a profound understanding of the philosophical meaning related with each theme. The inquire about comes about appear that Kuantan Singingi Batik includes a assortment of themes, each of which encompasses a profound philosophical meaning. A few themes that are frequently found incorporate flower, fauna and geometric themes. Botanical themes such as blossoms and clears out regularly symbolize ripeness, life and normal excellence. Faunal themes such as fowls and angle portray opportunity, mettle and nearby intelligence. In the interim, geometric themes reflect adjust, arrange and concordance between people and nature. The philosophical meaning contained in Kuantan Singingi Batik reflects the see of life of the Kuantan Singingi individuals who truly regard nature and the encompassing environment.